Microvascular heterogeneity exploration in core and invasive zones of orthotopic rat glioblastoma via ultrasound localization microscopy - Xing Hu; Gaobo Zhang; Yong Wang; Xiandi Zhang; Rong Xie; Xin Liu; Hong Ding (European Radiology Experimental)
Abstract Background We studied the microvascular structure and function of in situ glioblastoma using ultrasound localization microscopy (ULM). Methods The in vivo study was conducted via craniotomy in six Sprague–Dawley rats. Capillary pattern, capillary hemodynamics, and functional quantitative parameters were compared among tumor core, invasive zone, and normal brain tissue with ex vivo micro-computed tomography (micro-CT) and scanning electron microscopy. Correlations between quantitative parameters and histopathological vascular density (VD-H), proliferation index, and histopathological vascular maturity index (VMI-H) were evaluated. Kruskal–Wallis H, ANOVA, Mann–Whitney U, Pearson, and Spearman correlation statistics were used. Results Compared to the tumor core, the invasive zone exhibited higher microvascularity structural disorder and complexity, increased hemodynamic heterogeneity, higher local blood flow perfusion (p ≤ 0.033), and slightly lower average flow velocity (p = 0.873). Significant differences were observed between the invasive zone and normal brain tissue across all parameters (p ≤ 0.001). ULM demonstrated higher microstructural resolution compared to micro-CT and a nonsignificant difference compared to scanning electron microscopy. The invasive zone vascular density correlated with VD-H (r = 0.781, p < 0.001). Vessel diameter (r = 0.960, p < 0.001), curvature (r = 0.438, p = 0.047), blood flow velocity (r = 0.487, p = 0.025), and blood flow volume (r = 0.858, p < 0.001) correlated with proliferation index. Vascular density (r = -0.444, p = 0.044) and fractal dimension (r = -0.933, p < 0.001) correlated with VMI-H. Conclusion ULM provided high-resolution, noninvasive imaging of glioblastoma microvascularity, offering insights into structural/functional abnormalities. Relevance statement ULM technology based on ultrafast ultrasound can accurately quantify the microvessels of glioblastoma, providing a new method for evaluating the effectiveness of antiangiogenic therapy and visualizing disease progression. This method may facilitate early therapeutic assessment. Key Points ULM reliably captures the vascular structures and hemodynamic features of glioblastoma in rats. Micro-CT and scanning electron microscopy validated its effectiveness in microvascular non-invasion characterization. ULM is expected to effectively evaluate glioblastoma anti-vascular therapy response. Graphical Abstract